102 Neoadjuvant chemotherapy with uterine artery chemoembolization in the management of locally advanced cervical cancer: belarus experience. (13th November 2020) - Matylevich, O; Kosenko, I; Litvinova, T; Evmenenko, A
Abstract : Objective: To study the efficacy of neoadjuvant chemotherapy (NACT) with uterine artery chemoembolization (UACE) followed by radical surgery or radiotherapy in patients with locally advanced cervical cancer (LACC). Methods: Study included 55 primary LACC patients: 25 presented stage IIB (45.5%), 28 – IIIB (50.9%) and 2 – IVA (3.6%). Forty-seven patients had squamous cell carcinoma (85.5%), 7 – adenocarcinoma (12.7%) and one – undifferentiated cancer (1.8%). Patients underwent two courses of NACT: intravenous infusion of cisplatin and gemcitabine during first course and after 3 weeks transcatheter uterine artery infusion of gemcitabine, gelatin sponge particles were applied for UACE. After NACT, all patients underwent evaluation for response and operability. Those who were not amenable to surgery received radiotherapy. Results: Bilateral UACE was performed in 36 patients (65.5%) and unilateral – in 19 (34.5%). Patients who responded to NACT (42, 76.4%) underwent surgery: 40 patients had radical hysterectomy and 2 – anterior pelvic exenteration. After bilateral UACE surgery was performed in 83.3% (30/36), unilateral – in 63.1% (12/19) (p< 0.05). Radical surgery was performed in 38 (90.5%) of the patients. Patients who did not respond to NACT (13, 23.6%) underwent pelvic radiotherapy. The 5-year overall survival was 76.2±6.6% in patients receiving surgery and 23.1±11.7%% for those receiving radiotherapy (p <0.0011); the 5-year disease-free survival was 82, 7±6, 0% and 48, 6±16, 7%, respectively (p=0.028). Results: In LACC patients after NACT with UACE resection rate was 76.4%, the surgery was performed radically in most of the cases (90.5%), showing better survival benefits if followed radical surgery rather than radiotherapy.